2008
DOI: 10.1111/j.1440-1746.2008.05366.x
|View full text |Cite
|
Sign up to set email alerts
|

Waist circumference correlates with hepatic fat accumulation in male Japanese patients with non‐alcoholic fatty liver disease, but not in females

Abstract: Background and Aim: Abdominal obesity, a component of metabolic syndrome, is a major risk factor for non-alcoholic fatty liver disease (NAFLD). In recent worldwide definitions of metabolic syndrome, waist measurement has been proposed as a simple and useful estimate of abdominal obesity, taking into account gender differences in waist circumference. The present cross-sectional study investigated the correlation of hepatic fat accumulation and waist circumference in Japanese NAFLD patients to determine if there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 39 publications
(42 reference statements)
3
37
1
Order By: Relevance
“…VFA showed positive relationships with age ≥ 56, male gender, BMI ≥ 24. 4 ment for visceral fat accumulation, and the findings are in concordance with results from previous studies conducted within the Japanese population [10][11][12] . We focused on gender differences and the relationship between visceral fat accumulation and other clinical parameters.…”
Section: Factors Affecting Visceral Fat Accumulationsupporting
confidence: 91%
“…VFA showed positive relationships with age ≥ 56, male gender, BMI ≥ 24. 4 ment for visceral fat accumulation, and the findings are in concordance with results from previous studies conducted within the Japanese population [10][11][12] . We focused on gender differences and the relationship between visceral fat accumulation and other clinical parameters.…”
Section: Factors Affecting Visceral Fat Accumulationsupporting
confidence: 91%
“…In an earlier study [19], the severity of liver steatosis was correlated with the amount of visceral fat accumulation. In the present study, we found that the reduction in visceral fat accumulation by appropriate therapy might ameliorate liver steatosis and improve liver function in patients with NAFLD.…”
Section: Discussionmentioning
confidence: 96%
“…We have previously demonstrated a relationship between visceral fat accumulation and the development of IR in patients with NAFLD [3,13]. The present study was designed to examine the relationship between visceral fat accumulation and preclinical fatty liver in the general population, and the role of visceral fat accumulation in the histopathological progression of NASH in patients with NAFLD who underwent liver biopsy.…”
Section: Discussionmentioning
confidence: 99%